Research on the Integrated Operation Platform for Autonomous-rail Rapid Transit - WU Junliang; PENG Qin; ZOU Bin; ZHANG Hongbin (Kongzhi Yu Xinxi Jishu)
There are many kinds of modern rail transit systems, and the composition of each subsystem is complicated. Traditional rail transit operation and dispatch management system adopts separate system structure, which deploys and operates independently. It has many interfaces and complicated operation requirement. It is more and more difficult to meet the requirements of efficient operation. However, from operation’s point of view, it is still favorable to maintain the independence of each subsystem so as to facilitate troubleshooting. Therefore, traditional solution is difficult to meet the independence requirements. In order to ensure the safe and orderly operation of ART and improve the operation and scheduling efficiency, a set of unified ART integrated operation platform is developed, which integrates the functions of each subsystem through an unified user interface and human-computer interface, so as to simplify the operation of the staff and save labor cost. The system uses FEP as middle layer, which works as the interface between subsystem functions of different services and background process. The realization of this system greatly reduces the workload and labor intensity of operation manager, and reduces labor cost.